2020
DOI: 10.1016/j.tranon.2019.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Homologous Recombination Repair Deficiency and the Immune Response in Breast Cancer: A Literature Review

Abstract: The success of cancer immunotherapy with immune checkpoint blockade (ICB) has demonstrated the importance of targeting a preexisting immune response in a broad spectrum of tumors. This is particularly novel and relevant for less immunogenic tumors, such as breast cancer (BC), where the efficacy of ICB was more evident in the triple-negative (TNBC) subtype, in earlier stages, and in association with chemotherapy. Tumors harboring homologous recombination DNA repair (HRR) deficiency (HRD) are supposed to have a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 115 publications
5
56
0
1
Order By: Relevance
“…Due to the notable aggressive behaviour of TNBC, existing treatment options have limited or no efficacy against tumour metastasis 44,47 . Recently, Different molecular studies have allowed for the emergence of targeted therapies 48 , whereas others have evolved to explain mechanisms of resistance [49][50][51][52][53] . Several signalling pathways and biomarkers have been shown to be implicated in TNBC progression such as BAX/BCL2, HSP90α, EGFR, VEGF, survivin, CDK1, caspases, mTOR, and Ras/Raf/MEK/ERK 22,[52][53][54][55][56][57][58][59][60] .…”
Section: Discussionmentioning
confidence: 99%
“…Due to the notable aggressive behaviour of TNBC, existing treatment options have limited or no efficacy against tumour metastasis 44,47 . Recently, Different molecular studies have allowed for the emergence of targeted therapies 48 , whereas others have evolved to explain mechanisms of resistance [49][50][51][52][53] . Several signalling pathways and biomarkers have been shown to be implicated in TNBC progression such as BAX/BCL2, HSP90α, EGFR, VEGF, survivin, CDK1, caspases, mTOR, and Ras/Raf/MEK/ERK 22,[52][53][54][55][56][57][58][59][60] .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also suggest high responses in non -BRCA mutated cells. This could be explained by mutations in other genes belonging to HR, like ATM, ATR, RAD51, BARD1 [ 150 ], and by genomic instability like tumor allelic imbalance (TAI) and loss of heterozygosity (LOH), indicative of homologous recombination deficiency (HRD) [ 151 , 152 , 153 ]. A recent study by Mirza et al, analyzed four phase III clinical trials testing PARPi as monotherapy or in combination, evaluating both BRCA and HRD-tumors [ 151 ].…”
Section: Targeting Ddr To Defeat Cancermentioning
confidence: 99%
“…cluster of differentiation 244 IL-4 interleukin 4 BC breast cancer ILT2 leukocyte immunoglobulin-like receptor subfamily BRCA1/2 breast cancer type 1/2 susceptibility protein B member 1 CAMLs cancer associated macrophage-like cells JAK1/2 janus kinase 1/2 CD127 interleukin-7 receptor subunit alpha LAG3 lymphocyte-activation gene 3 CD14 cluster of differentiation trigger an immune response [25]. The identification of biomarkers is dependent on understanding the complex interaction between tumor and immune cells, and combinational therapies might be proposed to prime cold, nonimmunogenic tumors to increased immunogenicity, as thought to be possible by chemotherapy inducing antigen release [26] and by PARP inhibitors inducing higher mutational burden and activating PD-L1 expression [27,28]. It has already been shown that the lines of treatment are predictive for the response of BC patients to ICI [29] and due to the fact that HER2-positive and TNBC patients showed an increased benefit from ICI as compared to other BC subgroups [6,15], IHC detecting the hormonal receptors and HER2 in tumor tissue might be used as first hint for ICI response prediction.…”
Section: B4mentioning
confidence: 99%
“…However, in hereditary BRCA1/2 mutant BC and OC patients, TMB was not associated with the magnitude of immune response [92]. The promising effect of ICI in mismatch repair-deficient BCs might be due to the combinational regimen with PARP inhibitors [27], which were shown to induce PD-L1 expression [28,93]. BRCA mutations can be assessed by using cfDNA or genomic DNA of CTCs [94,95] as potential LB sources for immunogenicity.…”
Section: Specific Mutationsmentioning
confidence: 99%